2018
DOI: 10.1093/ser/mwy020
|View full text |Cite
|
Sign up to set email alerts
|

Extreme work hours in Western Europe and North America: diverging trends since the 1970s

Abstract: This article presents a political economy analysis of extreme work hours in 18 advanced Western economies since the 1970s. Empirically, it shows that the culture of long work hours has gained significance not only in the Anglo-Saxon but also in most Continental European welfare states. Theoretically, it provides an institutionalist argument against the neoclassical, or supply-side, point of view on the drivers of long work hours in post-industrial labour markets. It demonstrates that the choice to work long ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…With regard to working hours, Burgoon and Raess (2011) show that collective agreements at the establishment level mediate the impact of globalization indicators on standard weekly working hours in Europe. Similarly, Burger (2018) demonstrates that very long workweeks, with 50 hours and more, are less prevalent in countries with centralized collective bargaining. Finally, our findings resonate with those of Landivar (2015), who found that state regulations stipulating short standard work weeks and less maximum allowable weekly working hours lead to gender equality within couples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to working hours, Burgoon and Raess (2011) show that collective agreements at the establishment level mediate the impact of globalization indicators on standard weekly working hours in Europe. Similarly, Burger (2018) demonstrates that very long workweeks, with 50 hours and more, are less prevalent in countries with centralized collective bargaining. Finally, our findings resonate with those of Landivar (2015), who found that state regulations stipulating short standard work weeks and less maximum allowable weekly working hours lead to gender equality within couples.…”
Section: Discussionmentioning
confidence: 99%
“…It offers a theoretical rationale based on power that helps us to theorize on working hour differences. Further, the explanative power of this framework received empirical support in the comprehensive cross-country comparative studies by Burger (2018) and Eurofound (2016).…”
Section: The Framework Of Working Time Configurationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Their findings are mixed, particularly on whether a shorter working week has positive or negative effects on well-being, and the call for more in-depth research remains unanswered. Using different methods, particularly the ordered probit and logit models, scholars have investigated the worktime-satisfaction nexus based on various national-and regional-level surveys conducted in, for example, the US, UK, Germany, Australia, France, Korea, and the EU [14]. We review the literature below to explore the nexuses between working time and work satisfaction and job satisfaction and overall life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Work hours in the United States, along with Britain, are among the longest in the Organisation for Economic Co-operation and Development (OECD), though well behind those of Japan and Korea, and the ratio of extreme work hours is high (Burger 2018). Japanese business and conservative leaders cannot deny the work hour problem, though they typically blame government regulation or even the workers themselves.…”
Section: The United Statesmentioning
confidence: 99%